Pengaruh Perencanaan dan Fasilitas Kerja Terhadap Efektivitas Kerja Pegawai pada Puskesmas Batang Toru Kabupaten Tapanuli Selatan - Mahadi Siregar; Nur Ainun Hasibuan (EBISMA : Jurnal Ekonomi, Bisnis, Manajemen dan Akuntansi, 2026)
This study aims to determine the effect of planning and work facilities on employee work effectiveness at the Batang Toru Public Health Center, South Tapanuli Regency. The research method used is a quantitative approach with data collection techniques through questionnaires distributed to 71 respondents. Data analysis was conducted using validity and reliability tests, classical assumption tests, multiple linear regression, t-test, and F-test with the help of SPSS software. The results show that partially, planning has a significant effect on work effectiveness, while work facilities do not have a significant partial effect. However, simultaneously, planning and work facilities have a significant effect on work effectiveness. The coefficient of determination (R²) value of 0.509 indicates that 51% of work effectiveness is influenced by planning and work facilities, while the remaining 49% is influenced by other variables not examined in this study. Therefore, improving proper planning and providing adequate work facilities can enhance employee work effectiveness.